Sagot :
Answer:
3x-y = 13
Step-by-step explanation:
Using the slope intercept form
- y = mx+b
where m = slope and b = y-intercept
Given: m = 3
So ,
- y = mx+b
- y = 3x+b
Now. we solve for b by substituting the point (3,-4)
- y = 3x+b
- -4 = 3(3)+b
- -4 = 9 + b
- -4-9 = b
- -13 = b
Again substitute ,
- y = 3x+b
- y = 3x-13
Convert to standard form
- y = 3x-13
- -3x+y = -13
- 3x-y = 13
Therefore , the line is 3x-y = 13
[tex]\sf\gray{= = = = = = = = = = = == = = = = = = = = = =}[/tex]
[tex]\blue{ \huge \tt Answer: }[/tex]
y = 3/4 × - 37/4
or
- 3× + 4y = - 37
[tex]\sf\gray{= = = = = = = = = = = == = = = = = = = = = =}[/tex]
![View image Smartbabble](https://ph-static.z-dn.net/files/d03/68b0255cfd0383b073f97e96e54a05c9.jpg)